Deciphering the Cathode–Electrolyte Interfacial Chemistry in Sodium Layered Cathode Materials. Issue 34 (30th October 2018) - Mu, Linqin; Feng, Xu; Kou, Ronghui; Zhang, Yan; Guo, Hao; Tian, Chixia; Sun, Cheng‐Jun; Du, Xi‐Wen; Nordlund, Dennis; Xin, Huolin L.; Lin, Feng
Abstract: The ever‐increasing demand for stationary energy storage has driven the prosperous investigation of low‐cost sodium ion batteries. The inferior long‐term cycling stability of cathode materials is a significant roadblock toward the wide commercialization of sodium ion batteries. This study enlightens a path toward empowering stable sodium ion batteries through incisive diagnostics of the multiscale surface chemical processes in layered oxide materials (e.g., O3‐NaNi1/3 Fe1/3 Mn1/3 O2 ). The major challenges are unraveled in a promising sodium layered cathode material using a range of complementary advanced spectroscopic and imaging diagnostic techniques. It is discovered that the cathode–electrolyte interfacial reaction triggers transition metal reduction, heterogeneous surface reconstruction, metal dissolution, and formation of intragranular nanocracks. These surface chemistry driven processes are partly responsible for significant performance decay. This diagnostic study also rationalizes the elemental substitution and surface passivation methods that are widely applied in the field. The prepassivated and Ti‐substituted cathode materials allow for significantly improved cycling stability by inhibiting the metal dissolution. Therefore, incisively diagnosing the interfacial chemistry not only creates scientific insights into understanding sodium cathode chemistry, but also represents an advance toward establishing universal interfacial design principles for all alkali metal ion cathode materials. Abstract : Cathode–electrolyte interfacial reactions accompanied by transition metal reduction, surface reconstruction, metal dissolution, and formation of intragranular nanocracks are the origins of performance decay for sodium layered cathode materials. This pioneering effort of incisively diagnosing the interfacial chemistry creates scientific insights into understanding and improving the sodium cathode chemistry.